<The> Diversity as a factor effecting corporate culture and its impact on the culture differences by lewis model in Slovak and Chinese company - Turáková, Alexandra
Pojem podniková kultúra. Porovnanie Číny a Slovenska z hľadiska ich podnikovej kultúry.